Research Trends and Challenges in Intercultural Communication within Global Chinese Language Education: A Bibliometric and Systematic Review (2020–2025) - Sukma, Sukma; Dian Sari Unga Waru (Universitas Negeri Semarang, 2025)
Intercultural communication is a critical component in Chinese language education, where linguistic proficiency must be accompanied by cultural competence. This study explores research trends, key challenges, and conceptual gaps in intercultural communication within Chinese language education from 2020 to 2025. Using a Systematic Literature Review (SLR) combined with bibliometric analysis, 2,744 peer-reviewed articles were identified and examined from the Scopus database. Findings indicate an initial growth in research publications, peaking in 2024, followed by a sharp decline in 2025. China, the United Kingdom, and the United States dominate in terms of publication volume, while Southeast Asian countries such as Indonesia and Malaysia are showing growing engagement. Keyword analysis reveals a strong focus on “intercultural communication,” “language education,” and “foreign language learning,” often framed within Sinocentric perspectives. Despite increased scholarly attention, the field continues to rely on conventional theories that do not adequately address the dynamic nature of cultural identities. Pedagogical practices remain fragmented, with limited integration of critical literacy and culturally responsive teaching approaches. Existing assessment tools also lack the capacity to effectively measure the complexity of intercultural competence. The findings suggest a need for the development of inclusive, context-sensitive pedagogical models and more robust evaluation tools to enhance intercultural competence in global Chinese language education.